2021
DOI: 10.3389/fneur.2021.666481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Outcomes After Stent-Assisted Coiling of Cerebral Aneurysms With Laser-Cut and Braided Stents: A Comparative Analysis of the Literatures

Abstract: Introduction: Stent-assisted coiling (SAC) plays an important role in endovascular treatment of intracranial aneurysms (IAs). This comparative analysis examines the safety and efficacy of SAC in general and compares clinical and angiographic outcomes between laser-cut stents and braided stents.Methods: Relevant English-language studies were identified via a PubMed search for published articles regarding outcomes of SAC using laser-cut stents and braided stents published from 2015 to 2020. Data from 56 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…Closed-cell stent designs, on the other hand, contain the risk of poor wall apposition and kinking tortious vessel curves. We observed a relatively high rate of complete aneurysm obliteration (RROC I) of 78% in the whole study cohort, which is in line with previous studies investigating SACs ranging from 54–81% with different stent models [ 4 , 5 , 19 , 20 , 21 ]. In our study the rate did not differ between different stent models but was numerically higher in the closed-cell LEO+™ stent group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Closed-cell stent designs, on the other hand, contain the risk of poor wall apposition and kinking tortious vessel curves. We observed a relatively high rate of complete aneurysm obliteration (RROC I) of 78% in the whole study cohort, which is in line with previous studies investigating SACs ranging from 54–81% with different stent models [ 4 , 5 , 19 , 20 , 21 ]. In our study the rate did not differ between different stent models but was numerically higher in the closed-cell LEO+™ stent group.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, balloon-assisted coiling may have an advantage regarding the control of medical risk factors for periprocedural hemorrhage but increases the weight of ischemic risk factors. Additionally, the rates of ischemic events and intracranial hemorrhage after SAC in the literature differ around 5% and 2%, respectively [ 19 ]. In our case series, we observed low rates of hemorrhagic and ischemic events, highlighting the general safety of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of each stent type depends on structures or manufacturing processes, showing different behaviors in delivery method, neck protection, and flow diversion. When it comes to the SAC group, various clinical and angiographic outcomes in braided and laser-cut SAC for intracranial aneurysms have been observed in several studies ( 12 , 25 , 26 ). Nevertheless, the performance of these two stent types in terms of perioperative procedure-related complications is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The low-profile visualized intraluminal support improves flow diversion effect and promotes reendothelialization due to its higher metal coverage (23%) and smaller mesh (1 mm) compared with laser-cut stents, theoretically, which could promote delayed aneurysm thrombosis and obtain a favorable occlusion rate in long-term follow-up ( 34 ). Nevertheless, a recent systematic review showed that the follow-up complete occlusion and recurrence in the LVIS group were comparable with the laser-cut group ( P = 0.454, 0.056, respectively) ( 26 ). Lim et al ( 35 ) reported a cohort study and demonstrated similar outcomes in follow-up and recurrence rates between the LVIS group and the Enterprise group.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive meta-analysis stated that SAC using braided stents had initial and last follow-up favorable aneurysm occlusion rates of 85.5% and 91.9%, respectively. 27 The proportion of patients who underwent SAC for ruptured WNAs and had favorable clinical outcomes were reported as 66-88% in a literature review. 15 In our study, we observed that the angiographic and clinical outcomes in the SAC group were comparable to those in the literature.…”
Section: Discussionmentioning
confidence: 99%